Interconnection of electrospun nanofibers via a post co-solvent treatment and its open pore size effect on pressure-retarded osmosis performance - Park, Chul Ho; Bae, Harim; Kwak, Sung Jo; Jang, Moon Seok; Lee, Jung-Hyun; Lee, Jonghwi (Macromolecular research, 2016)
Design of support layer structures for asymmetric thin film composite membranes has drawn keen attention to improve the power density for salinity gradient power based on pressure-retarded osmosis. This study has interests on electrospun nanofiber-based support layers, and the effects of its open pore sizes are attractively stated. To control the open pore size, a counter charge deposition method was introduced. To retain the open pore size, all the nanofibers were interconnected by a post co-solvent treatment technology. For a thin film composite membrane, an interfacial polymerization was used to fabricate a polyamide active layer on the electrospun nanofiber-based support layers. It was found that although the maximum power density achieved with an open pore size of 2.4 μm 2 was 0.14 W/m 2 , it increased significantly up to 9.5 W/m 2 when the pore size was reduced to 0.65 μm 2 . The cause is the salt flux which increases with increasing the open pore sizes under applied pressures.